Implementasi E-Edition Modern Standard Arabic (MSA) dalam Pembelajaran Bahasa Arab - Ainun Syarifah (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2019)
The Language Development Center (P2B) is one of the institutions under management of UIN Sunan Ampel Surabaya. This program has responsibility in strengthening Arabic language competence for all students. The standardization of Arabic language competencies is an Arabic language learning intensification program that is managed by P2B. P2B has made various efforts in improving student competence in Arabic, one of it is by reformulating the Arabic Language learning model, namely by implementing online learning using the E-edition Modern Standard Arabic (MSA) program. The Intensive Arabic Language learning program is done twice a week which are divided into two study groups based on the language competency classifications students. All Intensive Arabic Instructors have different learning strategies, adjusting the characteristics and competencies of their students in each class. As a final test is conducted using an online test called Final Online Test (FOT), It means to measure the results of the Arabic language learning that has been done. The type of this research is a qualitative descriptive analysis research, with deep interview, documentation, group discussion forum as data collection technique.